The invention of mobile head loss apparatus - Abd Rahman, Misbahul Muneer; Roslan, Luqman Hakim; Shahrizan, Ahmad Shauqi Abrar; Md Zilzali, Ariff Haikal (Penerbit UTHM, 2020)
We might begin with a few general statements about fluid mechanics, the study of the motion of `fluids', meaning liquids and gases, and the effects of such motion [1]. Fluid motions are responsible for most of the transport and mixing (of materials or properties) that take place in the environment, in industrial processes, in vehicles, and in living organisms. In industrial processes, it is largely responsible for the rates at which many processes proceed, and for the uniformity of the resulting product.